Experiences of digital physiotherapy during pregnancy and after childbirth: A qualitative study - Frida Johnson; Sara Frygner Holm; Andrea Hess Engström (Internet Interventions)
Background: Pelvic girdle pain, low back pain, and pelvic floor dysfunction can affect women's mobility, quality of life, and well-being during pregnancy and the postpartum period. Digital interventions for treating perinatal depression and lifestyle changes have been studied. Research on digital physiotherapy for musculoskeletal issues related to pregnancy and the postpartum period is sparse. Methods: This qualitative study involved in-depth, semi-structured interviews with 19 participants, of whom six were pregnant and 13 had given birth. Participants were recruited from a private clinic in Sweden through convenience sampling and had received digital physiotherapy prior to the interviews. An interview guide with questions exploring participants' experiences of digital physiotherapy, including its impact on musculoskeletal issues and daily life, and their motivation for seeking digital healthcare was used. Data were analyzed using a qualitative content analysis with an inductive approach. Results: The analysis resulted in two main categories: Finding a new way into physiotherapy treatment and Personalized progress through tailored physiotherapy. These main categories encompassed four generic categories: Convenience and dissatisfaction motivators for digital physiotherapy, A dual experience – appreciated but not always comprehensive, Being involved in the rehabilitation process, and Perceived physical and mental improvements after digital physiotherapy. Conclusion: Digital physiotherapy was well-accepted and perceived as beneficial for managing musculoskeletal symptoms during pregnancy and after childbirth. High accessibility and flexibility were considered advantages. However, inability to undergo a physical assessment was a challenge. Digital physiotherapy may be recommended as a complement to usual care, particularly for women with limited access to a physiotherapist specialized in women's health. Future studies exploring digital physiotherapy's efficacy for musculoskeletal issues during pregnancy and after childbirth are highly recommended.